Incentive schemes for local government: Theory and evidence from comprehensive performance assessment in England - Benjamin Lockwood; Francesco Porcelli (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper studies Comprehensive Performance Assessment, an explicit incentive scheme for local government in England. Motivated by a simple theoretical political agency model, we predict that CPA should increase service quality and local taxation, but have an ambiguous effect on the efficiency of service provision. We test these predictions using a difference in difference approach, using Welsh local authorities as a control group, exploiting the fact that local authorities in Wales were not subject to the same CPA regime. To do this, we construct original indices of service quality and efficiency, using Best Value Performance Indicators. We estimate that CPA increased the effective band D council tax rate in England relative to Wales by 4%, and increased our index of service quality output also by about 4%, but had no significant effect on our efficiency indices. There is evidence of heterogeneous effects of CPA on efficiency, with some evidence that CPA impacted more on less efficient councils, and the 'harder test'; from 2005-8 having a much bigger effect. - local government ; incentives ; efficiency ; difference in difference ; DEA
Keywords: H10; H70; H77; C21; 330; Kommunalverwaltung; Performance-Management; Ökonomischer Anreiz; Wirkungsanalyse; Technische Effizienz; Schätzung; England